Is it time to start COVID-19 vaccination in pregnant women? - Muhammad Ilham Aldika Akbar (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHTS1. Pregnant women infected with COVID 19 have a higher risk of maternal fetal mortality and morbidity.2. The available evidences show a safety profile in all type of COVID vaccines in pregnancy.3. Vaccination in pregnant women will decrease pregnancy complications, adverse pregnancy outcomes, and maternal death risk.4. The benefit of COVID vaccination exceeds the potential risk in pregnant women.5. Pregnant women are strongly recommended to receive COVID vaccine. ABSTRACTCOVID-19 pandemic has been lasting for years, and pregnant women encounter an increased risk of mortality and morbidity. Until now, vaccine COVID-19 has been developed and shows a promising result. Unfortunately, pregnant women are consistently excluded from receiving a new vaccine. Because pregnant women are excluded from participating in a clinical trial of vaccines related to safety issues, this exclusion cycle prevents pregnant women from receiving the vaccine that may benefit them. In this review article, the author provides evidence, data, and the reason why vaccination of pregnant women should be started in Indonesia, at least in a clinical trial, especially for health workers and women with comorbidities.